Japan's foreign policy, 1945-2009 : the quest for a proactive policy - Tōgō, Kazuhiko, 1945- (Brill, 2010)
Now in its third edition. This is a fascinating insider account of postwar Japanese foreign policy written by a former senior Japanese diplomat. The author examines Japanese foreign policy as it approaches a crucial reorientation towards a more proactive policy stance. The book is exceptionally clear, accessible and interesting for anyone interested in modern Japan.